2010
DOI: 10.1111/j.1420-9101.2010.02087.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing hybridization hypotheses and evaluating the evolutionary potential of hybrids in mangrove plant species

Abstract: Natural hybridization is of marked importance from global to local biological diversity. In mangroves, species ranges overlap extensively with one another and species share a long overlap of flowering time. Although hybridization has been suggested, patterns of hybridization and the evolutionary potential of hybrids are not yet fully understood. This study provides molecular evidence for the parental origins and status of hybrids in the dominant mangrove genus Rhizophora based on comparisons of chloroplast and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 100 publications
0
25
1
Order By: Relevance
“…Recent molecular studies have confirmed that R. × lamarckii is a hybrid between Rhizophora apiculata and Rhizophora stylosa ; R . × annamalayana is a hybrid between R. apiculata and Rhizophora mucronata ; and R. selala is a hybrid between R. stylosa and Rhizophora samoensis in the Indo-West Pacific region [49]. Despite frequent hybridization in sympatric sites, reproductive isolation between all the parental species of Rhizophora is ensured by F 1 hybrid sterility.…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular studies have confirmed that R. × lamarckii is a hybrid between Rhizophora apiculata and Rhizophora stylosa ; R . × annamalayana is a hybrid between R. apiculata and Rhizophora mucronata ; and R. selala is a hybrid between R. stylosa and Rhizophora samoensis in the Indo-West Pacific region [49]. Despite frequent hybridization in sympatric sites, reproductive isolation between all the parental species of Rhizophora is ensured by F 1 hybrid sterility.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrids of Rhizophora (specifically R. ×lamarckii , R. ×selala , and R. ×annamalayana ) are not included in this study because these hybrids have been shown to be F 1s [81] and are sterile or have much reduced fertility [6,42]. Inclusion of hybrid individuals can create conflict between chloroplast and nuclear trees [81], and obstruct our goal of inferring biogeographic history of the genus. Individuals of Bruguiera gymnorrhiza , from the sister genus to Rhizophora , were used as outgroup to root phylogenetic trees.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to these structures, it is now evident that some unimodal hybrid zones may be entirely or largely composed of F1 hybrids, while other hybrid zones are trimodal, containing both parents and mainly F1s. The absence or low frequency of later generation hybrids in these hybrid zones is not surprising when F1s are sterile (e.g., Moccia et al, 2007;Lo, 2010;Twyford et al, 2015), but is unexpected when F1s are fully fertile as documented in several studies (e.g., Milne et al, 2003;Christe et al, 2016). The absence of post-F1 hybrids where F1s are fertile has been attributed to their reduced postzygotic, extrinsic fitness in ecotones relative to F1s, causing them to be outcompeted (Milne et al, 2003), or to a lower intrinsic fitness relative to F1s caused by expression of Bateson-Dobzhansky-Muller (BDM) incompatibilities and/or breakdown of coadaptive gene complexes following recombination .…”
Section: Structure Of Hybrid Zonesmentioning
confidence: 99%